Assessment of factors influencing the transfer efficiency in electrostatic spray coating process. (2022) - Kulothungan, S.; Lakshmanan, Poovazhagan; Krishnan, Parthiban; Palani, Sarangapani; Arumugam, Arun
Abstract: The electrostatic spray is one of the advanced coating methods that provide uniform and effective coating on the surfaces of the components. This method can reduce the limitations observed in conventional spray painting. The uniform layer of paint depends on various input parameters such as paint flow rate, disc air pressure, paint viscosity, and applied voltage. The design of experiment (DOE) tool optimizes the process parameters to achieve the expected or best coating combinations. The transfer efficiency is an essential factor that determines the quality of the surface coating. In this work, the DOE tool was used to increase the transfer efficiency and reduce the time taken for the coating process with optimized process parameters. The experimental test found that the combined effect of input responses has increased the efficiency of the coating up to 70 %. The determined Transfer efficiency is higher than the conventional method.